2016
DOI: 10.1007/s11423-015-9420-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing virtual and location-based augmented reality mobile learning: emotions and learning outcomes

Abstract: Research on the effectiveness of augmented reality (AR) on learning exists, but there is a paucity of empirical work that explores the role that positive emotions play in supporting learning in such settings. To address this gap, this study compared undergraduate students' emotions and learning outcomes during a guided historical tour using mobile AR applications. Data was collected in a laboratory (Study 1; N = 13) and outdoors (Study 2; N = 18) from thirty-one undergraduate students at a large North American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 36 publications
3
103
0
10
Order By: Relevance
“…The increasing popularity of MOOCs and other educational technologies, such as mobile learning environments (Harley et al 2016a), stand to gain significantly from integrating the interdisciplinary approaches that have been under development and evaluation in ALTs for years. This taxonomy thus provides an opportunity to organize and share some of these insights with both the intelligent tutoring system and artificial intelligence in education community as well as the broader educational technology community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing popularity of MOOCs and other educational technologies, such as mobile learning environments (Harley et al 2016a), stand to gain significantly from integrating the interdisciplinary approaches that have been under development and evaluation in ALTs for years. This taxonomy thus provides an opportunity to organize and share some of these insights with both the intelligent tutoring system and artificial intelligence in education community as well as the broader educational technology community.…”
Section: Discussionmentioning
confidence: 99%
“…ALT is a broad term that includes a variety of sophisticated learning environments such Harley et al 2016a) and simulations or virtual worlds (BioWorld; Lajoie et al 2013;Jarrell et al 2016). Although the above labels for different types of learning environments are helpful for identifying specific features, they are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that AR was the most effective tool among these tools in all aspects. Harley et al [73] explored using AR in history education. They organized a historical tour with mobile AR location-based application and examined students' emotions and learning outcomes.…”
Section: Using Augmented Reality In Graduate Educationmentioning
confidence: 99%
“…And the future information service is not just targeted at simply seeing and hearing [11][12][13]. Information service will be emotions-based, and its value will depend on communication with device by enabling the user to see, hear, touch, feel, and interact with the device.…”
Section: Resultsmentioning
confidence: 99%